2004
DOI: 10.1074/jbc.m310779200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Some Variants of Human β2-Microglobulin and Amyloidogenesis

Abstract: Three variants of human ␤ 2 -microglobulin (␤ 2 -m) were compared with wild-type protein. For two variants, namely the mutant R3A␤ 2 -m and the form devoid of the N-terminal tripeptide (⌬N3␤ 2 -m), a reduced unfolding free energy was measured compared with wild-type ␤ 2 -m, whereas an increased stability was observed for the mutant H31Y␤ 2 -m. The solution structure could be determined by 1 H NMR spectroscopy and restrained modeling only for R3A␤ 2 -m that showed the same conformation as the parent species, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 54 publications
8
85
0
Order By: Relevance
“…Materials-Recombinant ␤2m and R3A␤2m were prepared as described previously (14,19). The B subunit of ␣-crystallin was employed for all the experiments except for the DOSY measurements in which bovine eye lens ␣-crystallin (Sigma), composed of ϳ3:1 ␣A-/␣B-crystallin, was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Materials-Recombinant ␤2m and R3A␤2m were prepared as described previously (14,19). The B subunit of ␣-crystallin was employed for all the experiments except for the DOSY measurements in which bovine eye lens ␣-crystallin (Sigma), composed of ϳ3:1 ␣A-/␣B-crystallin, was used.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the fragment of ␤2m devoid of the N-terminal hexapeptide (⌬N6␤2m) that occurs to a significant extent (ϳ30%) in ex vivo deposits of the protein (13) has an enhanced tendency to aggregate and form fibrils, even at neutral pH (14). Furthermore, the Arg-3-to-Ala mutant of ␤2m (R3A␤2m) forms a folded structure very close to that of the wild-type protein, but it exhibits a spontaneous propensity to unfold, aggregate, and precipitate over a period of days to weeks (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19] Studies on 2-m illustrate a basic mechanism of amyloid fibrillation. Dialysis-related amyloidosis is a common and serious complication in patients receiving hemodialysis for more than 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that I T contains a non-native trans peptide bond between His-31 and Pro-32 that slowly converts into cis conformation during the final refolding step (3). The isomerization occurs with minor rearrangements of the protein toward the native structure from an already native-like state (3)(4)(5). The native-like intermediate has been proposed as the effective fibril-competent species (4,6).…”
mentioning
confidence: 99%